The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1590/s1415-47572007000600001
|View full text |Cite
|
Sign up to set email alerts
|

TaqI B1/B2 and -629A/C cholesteryl ester transfer protein (CETP) gene polymorphisms and their association with CETP activity and high-density lipoprotein cholesterol levels in a Tehranian population. Part of the Tehran Lipid and Glucose Study (TLGS)

Abstract: We examined the cholesteryl ester transfer protein (CETP) gene TaqI intron 1 B1/B2 polymorphism and the -629A/C CETP promoter polymorphism in respect to high-density lipoprotein cholesterol (HDL-C) in a healthy Iranian population taken from the Tehran Lipid and Glucose Study (TLGS). The relationship between CETP activity and HDL-C level was also determined along with body mass index, blood pressure and tobacco smoking status. PCR-RFLP used to amplify a segment of the CETP intron 1 TaqI (B2/B1) polymorphism fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 29 publications
2
6
2
Order By: Relevance
“…In comparison to B1B1 genotype, B2 hetero and homozygote subjects had respectively 2.26% and 7.36% higher levels of HDL-C. This positive role is in agreement with the results of the two other studies carried in Iran [43,45]. Thompson et al in their meta- analysis study, that covers the results of 92 studies in different ethnic groups with more than 113,000 subjects, have also found a 4.5% increase in HDL-C levels and a 0.9% and 2% decrease in LDL-C and TG levels respectively for each inherited B2 allele[44].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In comparison to B1B1 genotype, B2 hetero and homozygote subjects had respectively 2.26% and 7.36% higher levels of HDL-C. This positive role is in agreement with the results of the two other studies carried in Iran [43,45]. Thompson et al in their meta- analysis study, that covers the results of 92 studies in different ethnic groups with more than 113,000 subjects, have also found a 4.5% increase in HDL-C levels and a 0.9% and 2% decrease in LDL-C and TG levels respectively for each inherited B2 allele[44].…”
Section: Discussionsupporting
confidence: 90%
“…The frequency of the CETP "B2" allele in this study was 46.1% which is higher than the 38.21% previously found by Daneshpour et al[43] in a group of Tehran's residents. However, it is in accordance with the prevalence of 42% that was reported in White and East Asian populations[44].…”
Section: Discussioncontrasting
confidence: 80%
“…17 These observations are significantly important because low plasma HDL-C levels are associated with an increased risk of cardiovascular disease. Clinical evidence documents that an increase of 1% in the plasma HDL-C levels is associated with a reduction of 2% to 3% in cardiovascular morbidity and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…This could be attributed to industrialization of the country, modification of life style, unhealthy diet, decreased physical activity, and increased prevalence of hypertriacylglycerolmia, obesity and smoking [16]. Association of some genetic factors with low HDL-C levels has been studied in Iranians [30,31]. These results showed that there is a relation between low HDL-C level and some genetic factors.…”
Section: Discussionmentioning
confidence: 99%